Strategi Fundraising Program Koin NU di LAZISNU Desa Mrican Jenangan Ponorogo - Alvan Yahya Kusuma; Muhtadin Amri (Institut Agama Islam Negeri Ponorogo, 2024)
The zakat infaq alms collection program is an effort to fulfill religious obligations and support various social activities. One of the popular programs is the infaq box program. This research analyzes the collection strategy for the donation box program at LAZISNU Mrican. This research uses a qualitative approach with data analysis methods involving thematic analysis. The research results show that the fundraising strategies for the NU coin program at LAZISNU Mrican used were dialogue fundraising strategies, corporate fundraising strategies, multichannel fundraising strategies, and strategies for maintaining donor loyalty. Low levels of awareness, economic limitations, lack of knowledge, and field factors are inhibiting factors. Meanwhile, the supporting factors in the donation box program are community support, the majority of NU residents, and transparency. Raising ZIS funds through the NU coin program at LAZISNU in Mrican village can have a broad positive impact on the community, increasing social welfare and the independence of the people.